Effects of Creep Feed Pellet Diameter on Suckling and Nursery Pig Performance - A. B. Clark; J. A. De Jong; J. M. DeRouchey; M. D. Tokach; S. S. Dritz; R. D. Goodband; J. C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 26 litters of pigs (PIC 327 × 1050; initially 7.1 lb and 10 d of age) were used in a 31-d growth trial to evaluate the effects of creep feed pellet diameter on suckling pig and subsequent nursery pig growth performance. On d 10 of the suckling phase, sows and their litters were allotted to one of two dietary treatments by parity and pig weight in a completely randomized design with 13 replications per treatment. Starting on d 10, pigs were fed the same creep feed formulation, but pelleted using either a 1/8 in. (small) or 1/2 in. (large) die. Chromic oxide was included in the diets as a fecal marker, and fecal swabs were taken twice a day on d 14, 17, and 21 to determine the percentage of pigs that were consuming creep feed. On d 21, pigs were weaned, re-allotted to nursery treatments for 21 d, and fed in two phases. Phase 1 (d 0 to 7 post-weaning) treatment diets were the same diets as fed during the suckling period, with 50% of the pigs remaining on their previously allotted pellet diameter treatment. The other 50% of pigs were re-allotted to the opposite pellet diameter treatment in the nursery, creating a 2 × 2 factorial with the main effects of pellet diameter during suckling and pellet diameter during the nursery phase. A common meal Phase 2 diet (d 7 to 21) was fed to all pigs. During the suckling phase (d 10 to 21), litters of pigs fed the large creep feed pellet had decreased (P<0.03) pre-weaning mortality and tended (P<0.06) to have greater litter BW gain and litter ADG. There were no significant differences observed in pig BW, pig BW gain, litter CV, or pigs identified as creep feed eaters. From d 17 to 21 of suckling, pigs fed the large creep feed pellet had increased (P<0.05) average daily creep feed intake. During the nursery phase, no interactions were observed for Phase 1 (d 0 to 7) when experimental diets were fed. Feeding a large pellet during the nursery phase, regardless of previous creep feed treatment, increased (P<0.05) ADFI from d 0 to 4, 4 to 7, and 0 to 7. Pigs fed the large pellet in the suckling phase, regardless of pellet diameter fed during the nursery phase, had improved (P<0.01) ADG from d 0 to 7 after weaning. Results from this study indicate that feeding a large creep feed pellet may be correlated with reduced pre-weaning mortality. However, there is no improvement on individual suckling pig growth performance or percentage of pigs eating creep feed between feeding either a small or large diameter pellet. Feeding a large creep feed pellet improved F/G for the entire nursery phase, and feeding a large nursery pellet increased ADFI during the first week in the nursery.
Keywords: creep feeding; growth; pellet size; swine